2015
DOI: 10.3109/21678421.2015.1009466
|View full text |Cite
|
Sign up to set email alerts
|

Six SQSTM1 mutations in a Chinese amyotrophic lateral sclerosis cohort

Abstract: The purpose of this study was to identify SQSTM1 gene mutations, estimate survival based on the progression rate of the revised amyotrophic lateral sclerosis functional rating scale (ALSFRS-R) score (ΔFS), and characterize the relationships between SQSTM1 mutations and clinical phenotypes in Chinese ALS patients. We sequenced the SQSTM1 gene in 35 familial ALS patients, 436 sporadic ALS patients, and 384 healthy controls. SQSTM1 gene mutations were screened with PCR and direct sequencing; the correlations betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…Mutations in the SQSTM1 were previously associated with ALS. Interestingly, three of the same variants reported in ALS patients (Ala33Val, Val153Ile, and Pro392Leu)[ 33 , 34 , 40 45 ] were also detected in our population control cohort and are present at a similar rate in the ExAC database ( Table 3 ). The presence of these variants in control subjects not known to have ALS might partially undermine their proposed role in the pathogenesis of this neurodegenerative disease.…”
Section: Discussionsupporting
confidence: 73%
“…Mutations in the SQSTM1 were previously associated with ALS. Interestingly, three of the same variants reported in ALS patients (Ala33Val, Val153Ile, and Pro392Leu)[ 33 , 34 , 40 45 ] were also detected in our population control cohort and are present at a similar rate in the ExAC database ( Table 3 ). The presence of these variants in control subjects not known to have ALS might partially undermine their proposed role in the pathogenesis of this neurodegenerative disease.…”
Section: Discussionsupporting
confidence: 73%
“…Analysis of 348 ALS and FTLD missense mutations in 14 genes focusing on protein stability based on available 3D structures predicted that most of the missense mutations with destabilizing energies occur in the regions that control protein–protein interactions, and that the predicted destabilization is greater for ALS compared to FTLD mutations and correlates with disease progression. However, other ALS causative mutations, which span throughout the SQSTM1 gene, have been identified, namely E81K, N239K, G297S, E372D, P388S, and P392L, suggesting more complex functions of the protein in disease pathogenesis . Intriguingly, some SQSTM1 mutations are associated with reduced Nrf2 activation in FTLD/ALS , with pharmacological Nrf2 activators showing beneficial effects .…”
Section: Role Of Nrf2 In Autophagymentioning
confidence: 99%
“…Several studies conducted in China confirmed the association between intermediate CAG repeat expansions and ALS risk, rather than the phenotype, in Chinese population from different regions (Chen et al, 2011; Liu et al, 2013; Lu et al, 2015). Variants in SQSTM1 and OPTN were detected in around 1% of sALS Chinese patients respectively, but it will be necessary to carry out more functional studies to verify the pathogenicity of these variants (Chen et al, 2014; Li et al, 2015; Liu et al, 2016b; Yang et al, 2015). By contrast, mutations in some other genes previously reported to be linked to ALS, including VAPB, ANG, VCP, UBQLN2 and DCTN1 , had been found to be rare or absent in Chinese ALS patients (Huang et al, 2017; Liu et al, 2016b, 2017a; Soong et al, 2014; Zou et al, 2012, 2013b).…”
Section: Genetic Characteristics Of Chinese Als Patientsmentioning
confidence: 99%